2021
DOI: 10.47346/ijaesa.v2i2.85
|View full text |Cite
|
Sign up to set email alerts
|

The use of Mobile Augmented Reality in health education review

Abstract: This paper aims to present the analysis and synthesis of studies in Mobile Augmented Reality in health education, with a critical approach, and to develop suggestions for future researchers.  The use of Mobile Augmented Reality technology has shown recently an improvement in teaching and instructing methods, several scientific articles and researches showed how this new technology has a positive impact on education and improving the learning and teaching methods and also has a positive impact on student’s perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…In the study conducted to examine students' perceptions of their actual use of mobile learning, it was found that Mlearning had a good and constructive effect on their actual usage (Alturki and Aldraiweesh, 2022). The efficiency of mobile knowledge in health sciences has also been investigated as in educational sciences (Çakır and Djibril, 2021;Ibili, 2020). However, the compulsory use of M-learning technologies in health sciences has increased the necessity of studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted to examine students' perceptions of their actual use of mobile learning, it was found that Mlearning had a good and constructive effect on their actual usage (Alturki and Aldraiweesh, 2022). The efficiency of mobile knowledge in health sciences has also been investigated as in educational sciences (Çakır and Djibril, 2021;Ibili, 2020). However, the compulsory use of M-learning technologies in health sciences has increased the necessity of studies in this field.…”
Section: Introductionmentioning
confidence: 99%